2013
DOI: 10.1061/(asce)ee.1943-7870.0000716
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Leachate Collection Systems with Filter Separators in Municipal Solid Waste Landfills

Abstract: A numerical model is used to estimate the service life and clogging of gravel leachate drainage layers with a filter separator layer, such as those used in municipal solid waste landfills. A filter separator layer between the waste and the drainage layer is shown to reduce the leachate strength entering the gravel drainage layer and to extend the time that it takes to clog the drainage layer to the point when the leachate level exceeds the maximum design value (the service life). The filter layer is shown to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Vangulck et al developed a linear regression of the measured removal of Ca 2+ versus the calculated H2CO3 production (TIC generation in this study) and suggested that the yield coefficient (YH) reflected this relationship [16]. In the following studies, this fixed coefficient (YH) was adopted in the development of clogging predicting models [15,30]. However, the reaction path from biodegradation to chemical precipitation was concatenated and complicated.…”
Section: Clogging Processesmentioning
confidence: 83%
“…Vangulck et al developed a linear regression of the measured removal of Ca 2+ versus the calculated H2CO3 production (TIC generation in this study) and suggested that the yield coefficient (YH) reflected this relationship [16]. In the following studies, this fixed coefficient (YH) was adopted in the development of clogging predicting models [15,30]. However, the reaction path from biodegradation to chemical precipitation was concatenated and complicated.…”
Section: Clogging Processesmentioning
confidence: 83%
“…At present, sanitary landfill is one of the main methods of municipal solid waste (MSW) disposal in China [1][2][3]. The leachate produced by the landfill mainly consists of moisture contained in the landfill waste and the decomposition of organic matter in the waste [4]. Leachate is a high-concentration organic wastewater with a complex composition.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, a barrier system comprises two components (Rowe 2005;Rowe et al 2004): (a) a highly permeable leachate collection system to collect and remove leachate for treatment and (b) a low-permeability liner system to reduce leachate leakage through the liner into groundwater and surface water. The performance of leachate collection systems in the field scale has been numerically examined by Rowe and Yu (2012, 2013b, 2013c and Yu and Rowe (2013) using a sophisticated biogeochemical model ) calibrated using laboratory mesocosm tests (Rowe and Yu 2013a). A practical design method was also proposed by Rowe and Yu (2013c) to estimate the service life and to optimize the design of leachate collection systems.…”
Section: Introductionmentioning
confidence: 99%